Nonbanks, Banks, and Monetary Policy: U.S. Loan-Level Evidence since the 1990s - David Elliott; Ralf Meisenzahl; José-Luis Peydró; Bryce Turner (ZBW - Leibniz Information Centre for Economics, 2020)
We show that nonbanks (funds, shadow banks, fintech) reduce the effectiveness of tighter monetary policy on credit supply and the resulting real effects, and increase risk-taking. For identification, we exploit exhaustive US loan-level data since 1990s and Gertler-Karadi monetary policy shocks. Higher policy rates shift credit supply from banks to less-regulated, more fragile nonbanks. The bank-to-nonbank shift largely neutralizes total credit and associated consumption effects for consumer loans and attenuates the response of total corporate credit (firm investment) and mortgages (house price spillovers). Moreover, different from the so-called risktaking channel, higher policy rates imply more risk-taking by nonbanks.
Keywords: E51; E52; G21; G23; G28; 330; Nonbank Lending; Monetary Policy Transmission; Risk-Taking Channel